Campylobacter spp.: validação de metodologia qPCR e detecção em queijo Minas artesanal - Suzana Horta Fonseca (2023)
Artisanal Minas cheeses (QMA) are characterized by small-scale production, using milk from rural properties and following traditional techniques specific to each region. QMA is traditionally produced in the state of Minas Gerais and has been increasingly valued and consumed. Due to the lack of heat treatment in the raw material, this food can carry pathogenic microorganisms and/or their toxins, such as Salmonella spp., Staphylococcus aureus, Listeria monocytogenes and Campylobacter spp., bringing risks to the consumer health. Despite its high incidence worldwide, there is a data shortage on the occurrence of Campylobacter spp. in Brazil, mainly in dairy products. Commercially available kits only aimed at detection of Campylobacter in chicken meat and are not validated for dairy products. Based on this information, this work has two stages: the first aims to validate a kit for detecting Campylobacter using the real-time PCR (qPCR) technique in milk and cheeses made from raw milk; and the second, to investigate the occurrence of Campylobacter spp. and the microbiological and physical-chemical quality of 60 QMA available on the market, comparing those produced with and without inspection. In the first experiment, the BAX® qPCR system was tested against the ISO 10272-1:2017 standardized method for the parameters of relative level of detection, sensitivity, relative trueness and false positive ratio. The results indicate that the two methods showed equivalent results when an enrichment step in Bolton broth was added to the BAX® system. In the second experiment, the cheeses were analyzed for counts of total coliforms, E. coli, coagulase positive Staphylococcus, lactic acid bacteria, and the presence of staphylococcal enterotoxins, Salmonella spp., L. monocytogenes, and Campylobacter spp.; percentage of moisture, total solids, fat contents, chloride and pH. Regarding microbiological quality, Campylobacter, Salmonella, L. monocytogenes and enterotoxins were not detected in any sample. Only the coliform count values were significantly (p < 0.05) higher for the QMA group without inspection. For the other counts, no significant differences were observed. With regard to the physicochemical parameters, 85 % of the samples had moisture values below 45.9 g/100 g in the cheeses with inspection, while for the cheeses without inspection, only 30 % had adequate values, with a significant difference (p<0.05) between the two groups. This result influenced the total dry extract and fat contents, which also showed a significant difference. Lower moisture content reflects a more suitable maturation time, however, high counts of total coliform, E. coli, Staphylococcus coagulase positive, hygienic-sanitary indicators, were found in the QMA samples with and without government inspection, demonstrating the need for constant training to make producers aware of the importance of good production practices, from milking to marketing.